THE EFFICIENCY OF USING A SMART GREENHOUSE IN THE OMAD FARM IN THE YANGIBAZAR DISTRICT OF THE KHOREZM REGION - G’ulomov Saidasror Sayidaxmedovich; Rasulova Muxabbat Tishabayevna (Journals Park Publishing, 2023)
This article describes the methods of using a smart greenhouse in the Omad farm in the Yangibazor district of the Khorezm region, its operation in accordance with the climate and methods for obtaining such a high-quality and abundant harvest.
Keywords: agriculture, smart greenhouse, design, sensor, microclimate, exposure meter.